2019
DOI: 10.1515/multi-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

“Successful” migration, (English) language skills and global inequality: The case of Bangladeshi migrants to the Middle East

Abstract: Migration has become a vital element of the Bangladeshi economy, which has led to an increasing focus on providing Bangladeshis with the skills needed on the international labour market. English is often cited as one of these skills, and previous research has shown that a primary reason why Bangladeshis wish to learn English is due to its perceived value for pursuing work abroad (Erling, Elizabeth J., Philip Seargeant, Mike Solly, Qumrul H Chowdhury, & Sayeedur Rahman. 2012. Attitudes to English as a langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Future research should assess the impact of language pro ciency (both English and French) on the occupational success of immigrants in the Canadian labor market. Erling et al (2019) investigated Bangladeshi immigrants' successful migration in the Middle East and noted that migration is a vital element of the Bangladeshi economy, which has led to an increasing focus on providing Bangladeshis with the skills needed in the international labor market. English is often cited as one of these skills that provides economic bene ts to migrants (Erling, Qumrul, Solly, & Seargeant, 2019).…”
Section: Immigrants' Occupational Perceived Benefits Of the Elsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should assess the impact of language pro ciency (both English and French) on the occupational success of immigrants in the Canadian labor market. Erling et al (2019) investigated Bangladeshi immigrants' successful migration in the Middle East and noted that migration is a vital element of the Bangladeshi economy, which has led to an increasing focus on providing Bangladeshis with the skills needed in the international labor market. English is often cited as one of these skills that provides economic bene ts to migrants (Erling, Qumrul, Solly, & Seargeant, 2019).…”
Section: Immigrants' Occupational Perceived Benefits Of the Elsmentioning
confidence: 99%
“…Some studies, such as Lindley (2002), Schellekens (2001), and Casale and Posel (2011), argue that language skills, especially English communication competence, have a positive effect on job opportunities, job-changing chances, and earnings. The necessity of English language skills in the workplace for Bangladeshi immigrants has been a subject of increasing concern for the country's economic development (Erling et al, 2019). The relative advantage of English language skills is greater for those in the top quarter of earnings, while greater penalties exist for immigrants with low levels of language pro ciency at the upper end of earnings (Boyd & Cao, 2009).…”
Section: Impact Of English Language Skills On Immigrants' Earningsmentioning
confidence: 99%
“…Luo and Shenkar's (2006) findings suggest that employees with higher levels of English proficiency are more likely to be involved in significant projects and decision-making processes, thereby enhancing their career growth opportunities. Another critical angle is presented by Erling et al (2019), who investigated the role of English proficiency in the context of global labor migration. Their study revealed that in many cases, proficiency in English can compensate for the lack of local language skills in the destination country, particularly for skilled professionals.…”
Section: Literature Review English Language Proficiency and Global Jo...mentioning
confidence: 99%